Effects of frequency, temperature, and dc bias electric field on the dielectric properties of methylammonium lead iodide from the perspective of a relaxor-like ferroelectric - Minussi, F. B. [UNESP]; Reis, S. P. [UNESP]; Araújo, E. B. [UNESP] (Elsevier, 2021)
This work reports dielectric properties of methylammonium lead iodide as a function of frequency, temperature, and dc bias electric field studied in terms of grain and grain boundary contributions. These results were analyzed from the perspective of a relaxor-like ferroelectric nature. The temperature dependence of dielectric permittivity at different frequencies showed a wide dispersion in the vicinity of the tetragonal-cubic phase transition, suggesting a relaxor ferroelectric feature after excluding artifacts as Maxwell-Wagner effects and dc contributions. The results from plots of the Vogel-Fulcher and the modified Curie-Weiss laws indicate the existence of a freezing temperature of the dipoles responsible for the relaxor character of the material (Tf ∼ 270 K) and a diffuse phase transition at high temperatures (γ ∼ 1.52-1.74). Measurements on heating and cooling protocols under a dc bias electric field suggest field-induced polarized domains like relaxor ferroelectric. The observed signatures of transitions between non-ergodic and ergodic relaxors to ferroelectric states were attributed to polar nano regions dynamics, suggesting a critical electric field around 0.03 kV cm−1.
Keywords: Dielectric properties; Ferroelectricity; Halide perovskite; Relaxor